The Effectiveness of Writing Short Story Texts Using E-Modules Based on Electronic Publication for Senior High School - Kristia Apriyani; Ernalida Ernalida; Didi Suhendi (STAI Hubbulwathan Duri, 2025)
The integration of digital technology into education necessitates innovative learning tools that go beyond traditional textbooks. One such innovation is the use of electronic modules (e-modules), particularly those based on Electronic Publication (EPUB) formats, which offer interactive and accessible learning experiences. This study investigates the effectiveness of EPUB-based e-modules in improving students' ability to write short story texts.This descriptive quantitative study involved 28 grade XI students from a senior high school. The research employed a pretest-posttest design to measure students’ performance in writing short story texts before and after using the EPUB-based e-module. Data were collected using a performance-based writing test assessed through a standardized rubric. Statistical analysis included descriptive statistics, normality tests, and a paired sample t-test.The average student score increased from 56.43 (pretest) to 79.43 (posttest) after using the EPUB-based e-module. The results of the paired t-test indicated a statistically significant difference between pretest and posttest scores (p = 0.000 0.05), confirming the effectiveness of the e-module in enhancing students’ writing skills.The findings demonstrate that EPUB-based e-modules are effective teaching tools for improving students’ ability to write short stories. Their interactive and flexible design supports better engagement and learning outcomes. This study recommends further development and integration of EPUB-based materials in language learning to promote digital literacy and writing proficiency.